The 2019 Indian Elections and the Ruralization of the BJP. (December 2019) - Maiorano, Diego
The Indian general elections occurred amid a widespread and severe agricultural crisis. Many analysts thought that this could have a substantial impact on the incumbent Bharatiya Janata Party's (BJP) prospects to remain in office. This article, using post poll data, analyses the voting behaviour of two key sections of the electorate, the rural poor and the farmers. It shows that the BJP drew substantial support from both categories, across caste and class. Far from being a party of the urban upper classes and castes, the results of the 2019 elections mark the culmination of a decades-long process of ruralization and 'proletarianization' of the party.